Nitric Oxide Regulates Neurogenesis in the Hippocampus following Seizures. (26th October 2015) - Carreira, Bruno P.; Santos, Daniela F.; Santos, Ana I.; Carvalho, Caetana M.; Araújo, Inês M.
Abstract : Hippocampal neurogenesis is changed by brain injury. When neuroinflammation accompanies injury, activation of resident microglial cells promotes the release of inflammatory cytokines and reactive oxygen/nitrogen species like nitric oxide (NO). In these conditions, NO promotes proliferation of neural stem cells (NSC) in the hippocampus. However, little is known about the role of NO in the survival and differentiation of newborn cells in the injured dentate gyrus. Here we investigated the role of NO following seizures in the regulation of proliferation, migration, differentiation, and survival of NSC in the hippocampus using the kainic acid (KA) induced seizure mouse model. We show that NO increased the proliferation of NSC and the number of neuroblasts following seizures but was detrimental to the survival of newborn neurons. NO was also required for the maintenance of long-term neuroinflammation. Taken together, our data show that NO positively contributes to the initial stages of neurogenesis following seizures but compromises survival of newborn neurons.